Kajian Potensi Risiko Kecelakaan pada Stasiun LRT Palembang dengan Analisis Semi-Kuantitatif - Rindiani, Rahma Indah; Usman, Kristianto; Kustiani, Ika; Siregar, Amril Ma'ruf (Universitas Lampung, 2023)
LRT is a mass transportation facility that supports public mobility, reduces air pollution and alleviates traffic congestion, also decreases public transportation cost. Risk management is very important in LRT to ensure the safety and security for users and employees services. This research aims are to identify and determine the potential risks of accidents based on each variable, also to know the level of accident risk that may impact users and employees safety on LRT Palembang. This research involves questionnarie surveys and semi-quantitative data analysis, also makes the accident risk profile for LRT Palembang. Based on data analysis, users risk profile score with 9 variables, 5 variables result in low risks with 4-8% percentage, and 4 other variables result in medium risk with 12-20% percentage. Operators risk profile score with 10 variables, 3 variables result in low risk with 8% percentage, and other 7 variables result in medium risk with 12-20% percentage.